Anemia, depression, and suicidal attempts in women: Is there a relationship? - Nastaran Eizadi-Mood; Raana Ahmadi; Sara Babazadeh; Ahmad Yaraghi; Massoumeh Sadeghi; Payam Peymani; Ali Mohammad Sabzghabaee (Journal of Research in Pharmacy Practice, 2018)
Objective: Suicide is a social health problem worldwide. Anemia has been associated with depression. Since it remains debated whether anemia is associated with suicide independently of depression, we evaluate this probable association in women who attempted suicide through acute poisoning. Methods: The study design was cross-sectional and performed on women who attempted suicide through intentional poisoning with age more than 18 years old. Different variables were evaluated and compared in patients with respect to anemia, depression, other psychiatric diseases and history of suicide. Independent t-tests and binary logistic regression were used for statistical analysis. Findings: Nearly 26.2% of the women had anemia (n = 55). Most women with anemia were in the age group of 20–40 years (68.8%). 52.2% of the women were married. Mixed-drug poisoning was the most common (60.1%) followed by pesticide (8.9%), and antipsychiatric medications (8.4%). There was a significant difference in duration of hospitalization between anemic and nonanemic patients. Nearly 72.7% of the patients survived without complications. Anemia and depression were not significant predictive factors for depression and suicide. However, in our patients, the presence of other underlaying psychiatric disorders was a risk factor for suicidal attempt through acute poisoning. Conclusion: In women who attempted suicide through acute poisoning, anemia and depression were not predicting factors for suicide. However, the presence of other underlying psychiatric psychiatric disorders had a predictive value for the outcome of treatment. Length of hospital stay was also correlated with anemia.